Supporting Educators in the Design of Constructionist Learning Environment Scenarios: a Framework - Nicastro, Flavio; Baranauskas, M. Cecília; Torres, Ricardo (Anais do Workshop de Informática na Escola (WIE), 2019)
The adoption of Hands-On/Heads-In activities associated with computational thinking (CT) development has received considerable attention in academic discussions. While the subject of CT is not new, the proposal of environments to support educators in the design and conduction of activities in educational contexts are hardly discussed in the mainstream literature. Hands-on/Heads-In activities are an essential aspect of Constructionism, proposed by Seymour Papert in the 80's and still worked on by his colleagues and followers in different types of practices. In this work, we contribute with the proposal of a framework to support the design of educational practices based on the principles of Constructionism and Creative Learning, in which Hands-On/Heads-In activities underlie the use of technology.